Treatment of giant cavernous aneurysm in an elderly patient via extracranial–intracranial saphenous vein bypass graft in a hybrid operating room: A case report. Issue 14 (April 2018) - Xin, Can; Zhang, Jianjian; Li, Zhengwei; Xiong, Zhongwei; Yang, Bangkun; Wu, Xiaolin; Wang, Hao; Zou, Yichun; Wu, Rongqing; Zhao, Wenyuan; Chen, Jincao
Abstract: Rationale: Extracranial–intracranial saphenous vein bypass (EC-IC SVB) remains indispensable for treating giant cavernous aneurysms. We report an unusual case of a giant cavernous aneurysm in an elderly patient treated with EC-IC SVB in a hybrid operating room. Immediately following proximal ligation of the internal carotid artery (ICA), she suffered an acute intraoperative encephalocele. Patient concerns: A 71-year-old woman had suffered from severe headache and double vision for 4 months. Diagnoses: The woman was diagnosed with a right giant cavernous aneurysm. Interventions: She was treated with an EC-IC SVB with therapeutic ICA occlusion in the first biplane hybrid operating room in China. Just after proximal ligation of the ICA, she developed an acute encephalocele, and immediately underwent decompressive craniectomy. During the surgery she underwent 3 angiographic explorations. Outcomes: After surgery, the aneurysm disappeared, and the graft was patent. Postoperative computed tomography and computed tomography angiography indicated a cranial defect and graft patency. Lessons: Although a hybrid operating room could improve the patency of grafts, the timing of ICA ligation for giant cavernous aneurysm via EC-IC bypass deserves further discussion. Second-stage ICA occlusion could offer an alternative for elderly patients requiring such treatment. In addition, cranial flap removal could prevent further neurologic deficits in a case of acute intraoperative encephalocele.